2017
DOI: 10.14777/uti.2017.12.1.28
|View full text |Cite
|
Sign up to set email alerts
|

Recent Antimicrobial Susceptibilities for UropathogenicEscherichia coliin Patients with Community Acquired Urinary Tract Infections: A Multicenter Study

Abstract: Purpose: The aim of this study was to determine the prevalence and disease-specific antimicrobial susceptibility of Escherichia coli in urinary tract infections (UTIs). Materials and Methods: A total of 862 patients older than 18 years of age, who were diagnosed with UTI between January 2013 and December 2015, were included. The results of urine culture, prevalence of extended-spectrum beta lactamase (ESBL)-producing E. coli, and antimicrobial susceptibility by disease were also examined. Results: A total of 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 18 publications
0
16
0
1
Order By: Relevance
“…Resistance patterns also differ across regions [ 42 ]. In 2006, the antibiotic resistance of E. coli isolated from cystitis to ciprofloxacin was 24.6% in Seoul, 40.0% in Gyeongsang Province, 14.7% in Gyeonggi Province, and 32.1% in Chungcheong Jeolla Province [ 40 ].…”
Section: Clinical Practice Guidelines By Specific Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Resistance patterns also differ across regions [ 42 ]. In 2006, the antibiotic resistance of E. coli isolated from cystitis to ciprofloxacin was 24.6% in Seoul, 40.0% in Gyeongsang Province, 14.7% in Gyeonggi Province, and 32.1% in Chungcheong Jeolla Province [ 40 ].…”
Section: Clinical Practice Guidelines By Specific Diseasesmentioning
confidence: 99%
“…However, it is difficult to apply the same cost-effectiveness concept in Korea where the standard treatment of acute uncomplicated cystitis has been changed to 3 days of empirical antibiotic treatment, and the fees for outpatient examinations, the dipstick test, and urine culture test are relatively inexpensive compared with those in the United States and Europe. According to recent data, approximately 24.6% of E. coli inducing community-acquired UTIs produce ESBL [ 42 ]. Therefore, systematic analysis is needed to investigate whether maintaining empirical antibiotic treatment without assessing antibiotic resistance of causative bacteria through a urine culture test would be appropriate in terms of treatment outcomes and prognoses.…”
Section: Clinical Practice Guidelines By Specific Diseasesmentioning
confidence: 99%
“…The pooled prevalence of ampicillin was low-at 30.7%-in this study, with regions A and B below 30%. Similar susceptibilities to ampicillin are seen in adult studies in Korea: one study conducted during 2010-2014 showed 35.3% susceptibility to ampicillin [17], and another study from 2013-2015 showed 30.4% [18]. A meta-analysis on the global prevalence of antibiotic resistance in pediatric UTIs showed similar low susceptibilities, where UTIs caused by E. coli showed a pooled prevalence of 46.6% in OECD countries and 20.2% in non-OECD countries [9].…”
Section: Discussionmentioning
confidence: 60%
“…İstatistiksel (2,30) . Kore'de 2016 yılında yayınlanmış çok merkezli bir çalışmada toplum kökenli üriner sistem infeksiyonlarından izole edilen E.coli suşlarında GSBL pozitiflik oranı % 24.6 olarak bulunmuş (17) . Benzer özelliklere sahip, 2018 yılında Meksika'da yapılmış başka bir çalışmada ise E.coli suşlarında GSBL pozitiflik oranı % 31.3 bulunmuştur (10) .…”
Section: İstatistiksel Değerlendirmeunclassified